(7w-13)+(-6w-7)=

Simple and best practice solution for (7w-13)+(-6w-7)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (7w-13)+(-6w-7)= equation:


Simplifying
(7w + -13) + (-6w + -7) = 0

Reorder the terms:
(-13 + 7w) + (-6w + -7) = 0

Remove parenthesis around (-13 + 7w)
-13 + 7w + (-6w + -7) = 0

Reorder the terms:
-13 + 7w + (-7 + -6w) = 0

Remove parenthesis around (-7 + -6w)
-13 + 7w + -7 + -6w = 0

Reorder the terms:
-13 + -7 + 7w + -6w = 0

Combine like terms: -13 + -7 = -20
-20 + 7w + -6w = 0

Combine like terms: 7w + -6w = 1w
-20 + 1w = 0

Solving
-20 + 1w = 0

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '20' to each side of the equation.
-20 + 20 + 1w = 0 + 20

Combine like terms: -20 + 20 = 0
0 + 1w = 0 + 20
1w = 0 + 20

Combine like terms: 0 + 20 = 20
1w = 20

Divide each side by '1'.
w = 20

Simplifying
w = 20

See similar equations:

| x-3=-1.25y | | f(-1)=4x-2x | | t+8t= | | f(2)=16x-2x | | 6x^2-84x+160=0 | | Y=-0.6(3)+0 | | 3sin^2x-3sinx-2=0 | | K+8=6(k-11) | | 14-2x=20-5x | | (10a+7)(3a-4)=0 | | 3y+15x=6 | | -8a+3a=15 | | 99=(w+2)(w) | | 6p-10q= | | f(-1)=16x-2x | | 5n-3=-188 | | 2b-3.4=-1.74 | | 121/8+f=194/5 | | c=50i^2+2000 | | f(0)=16x-2x | | 7(6-x)=-28 | | 6x^2-2x^2-2=-9x+1 | | 3.6=6.4-0.7X | | 8x-8=-136 | | 0=cos(4x) | | (fx)=4 | | 22.50=4g+3.54 | | f(x)=16x-2x | | 8+5(s+5t)= | | 0=4cos(4x) | | 2t+4+8u+2t= | | H(t)=-16t^2+64t+ho |

Equations solver categories